KAJIAN KEAMANAN PANGAN INDUSTRI TAHU KALIPUTIH BERDASARKAN HYGIENE DAN SANITASI DI KECAMATAN PURWOKERTO TIMUR - Faizah; Erawati, Rara; Raharditya, Carantia; Rini, Poppy Ambar; Hafizhi, Alif; Fauziyyah, Yumna Nurul; Muzakiyah, Lukvinda Asfi; Latifasari, Nurul (Journal of Technology and Food Processing (JTFP), 2024)
Tofu is a staple food in Indonesia, widely consumed and produced by small and medium-scale industries using simple methods. However, these industries face significant food safety challenges, primarily due to producers' limited knowledge and skills in hygiene and sanitation practices. This study was conducted in a small-scale tofu industry in Kaliputih Village, Banyumas Regency, to assess food safety practices related to personal hygiene, food hygiene, sanitation, raw material quality, processing room layout, and waste management. The findings revealed inadequate personal hygiene practices, including handwashing and the use of clean clothing. Equipment and raw material washing processes did not meet hygiene standards, and the processing room layout increased the risk of cross-contamination. The use of unsafe well water and improper wastewater treatment practices contributed to environmental pollution. Additionally, the tofu industry lacked a valid business license, raising legal and operational risks. Proposed solutions include implementing stricter sanitation practices, using clean water, improving wastewater treatment, and obtaining official permits to enhance food safety standards and protect consumer health. This study aims to contribute to improving tofu industry practices and ensuring the safety of its products for consumption.